Overcoming dualisms: socio-productive trayectories in the analysis of horticultural social structure's transformations in La Plata - Waisman, María Alejandra (Centro de Historia Argentina y Americana, 2011)
The present article presents the main guidelines of the theorical and methodological strategy used in the underway investigation about horticultural social structure's transformations in La Plata's city in the last 20 years. This approach tries to overcome the dualism action-structure and individual-society, thinking them as being complementary aspects in the analysis of social reality. The contributions and limitations of two paradigms which are pronounced as antagonistic in explaining social behavior and the theories seeking to reconcile both approachs are analized. The trajectory concept is proposed as mediating concept used to bring together the historical process, the structural constrictions and the human agency. Linked to the teorical approach a qualitative metodological strategy was implemented based on semi-structured interviews and participant observation. Finally, this article argues that the major transformations that took place during the '90s in the social space investigated , affected the social status of horticultural producer.